Artificial intelligence assistance in English for communication competence of english for specific purposes - Muchamad Muchibbuddin Waly; Aniqotul Milla Zakiyyah (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2024)
This study scrutinizes the role of artificial intelligence (AI) tools in enhancing English for Communication competence among undergraduate students in English for Specific Purposes (ESP) courses, specifically focusing on students in communication study programs in Indonesia. It examines students' attitudes, perspectives, and experiences with AI tools in improving English communication skills and aims to uncover AI integration's perceived benefits and challenges. A sequential explanatory mixed-methods design collected data from thirty-one undergraduate students using a Likert-scale questionnaire followed by semi-structured interviews to provide more detailed insights. Findings from the descriptive statistical analysis indicate that most students expressed positive reactions to using AI tools to support their communication competence. Students responded with benefits such as personalized learning experiences, real-time feedback, and improved interpersonal communication, public speaking, and business-related communication. However, concerns were raised regarding AI's reliability, data privacy, potential over-reliance on AI, and limited enhancement of creativity and critical thinking skills. In English classrooms, where integrating technology in language learning is increasingly prioritized, these findings suggest that AI tools can be valuable resources for developing communication skills among ESP students. To maximize their benefits, educational institutions should establish clear guidelines, promote critical engagement with technology, and provide adequate instructor support to help students navigate AI-related challenges.